Open Data as a Tool for Enhancing Corporate Social Responsibility - Blatnik, Staša; Kljajić Borštnar, Mirjana; Pucihar, Andreja (Organizacija in organiziranje, 2025)
Over the past two decades, since the emergence of the open data concept, its importance for society has grown, providing greater transpareny into organizational operations. Data published by public sector organizations enables public participation in governance processes as well as an oversight of public funding. Additionally, it has become evident that open data represents a significant opportunity for private sector organizations as well. By opening its data to engage the public, organizations demonstrate their commitment to corporate social responsibility and sustainable business practices. At the same time, this approach creates opportunities for establishing new partnerships and, consequently, new business opportunities. In this study, we will review the existing literature on corporate social responsibility and how organizations can achieve it through the publication of open data. We will focus on the challenges companies face when opening business data to the public and the opportunities that arise from doing so.